2007
DOI: 10.1002/adsc.200700196
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Catalyst and Co‐Catalyst Design in Olefin Polymerization Catalysis: Transferable Dianionic Ligands for the Activation of Late Transition Metal Polymerization Catalysts

Abstract: Treatment of nickel and palladium a-diimine catecholate complexes with alkylaluminum catecholates leads to active ethylene polymerization catalysts. Comparison of the catalytic activities achieved with combinations of a-diimine catecholate or halide complexes as catalyst precursors with different activators (MMAO or alkylaluminum catecholates) reveals that the presence of the catecholate ligand in both catalyst components is beneficial for achieving high activity levels at very low M/Al ratios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 49 publications
(26 reference statements)
2
16
0
Order By: Relevance
“…The synergistic existence of donor and acceptor organic parts in the coordination sphere of the metal center is a distinctive feature for a wide range of LL'CT chromophores. The acceptor moiety is usually represented by a neutral redox form of α-diimines (Scheme 1) with significant steric hindrances [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] and/or a rigid carbon skeleton [13,15,[25][26][27]. Thus, it provides the required planarity of the complex's structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synergistic existence of donor and acceptor organic parts in the coordination sphere of the metal center is a distinctive feature for a wide range of LL'CT chromophores. The acceptor moiety is usually represented by a neutral redox form of α-diimines (Scheme 1) with significant steric hindrances [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] and/or a rigid carbon skeleton [13,15,[25][26][27]. Thus, it provides the required planarity of the complex's structure.…”
Section: Introductionmentioning
confidence: 99%
“…(1) treatment of the transition metal compound with a quinone type ligand to generate a catecholate-containing intermediate (redox process) [15]; (2) an exchange reaction with the participation of the catecholate precursor and α-diimine. The principal peculiarity of the second method (most frequently used) is in the reverse order of the introduction of ligands into the coordination sphere of the metal center (compared to the first technique) [11][12][13]15,17,19,22,25,35,44,46]. The third combined method is the "one-pot" synthesis [16,36], which was applied to obtain the complex 1 described in ref.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of nickel-based α-diimine catalysts, it was found that alkyl substituents at the aniline derived moieties were capable of exerting a significant influence on the polymerization activities and polymer microstructures. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Typically, high molecular weight, branched polyethylene can be obtained by tuning of the sterics/electronics associated with the alkyl substituents.…”
Section: Introductionmentioning
confidence: 99%
“…We have found two structurally characterized diazabutadiene nickel catecholates: (1,4-bis-(2,6-di-isopropylphenyl)-2,3-dimethyl-1,4-diazabutadiene-1,3)(3, 4,5,6-Cl 4 -catecolato)nickel and (1,4-bis-(2,6-di-methylphenyl)-2,3-dimethyl-1,4-diazabutadiene-1,3)(3,4,5, 6-Cl 4 -catecolato)nickel which were used as precursors for olefin polymerization catalysts. 7 Reversible interconversion of redox isomers was observed in complex (N,N ′ -bis(3,5-di-tert-butyl-salicylidene)-1,2cyclohexanediamino)nickel cation. 8 It is the equilibrium between Ni(III)-phenolato form of complex (at low temperature) and Ni(II)-phenoxyl radical one (at ambient temperature).…”
Section: Introductionmentioning
confidence: 99%